Current understanding of RAD52 functions: Fundamental and therapeutic insights - Gottifredi, Vanesa (2020)
In this Special Issue, we would like to focus on the various functions of the RAD52 helicase-like protein and the current implications of such findings for cancer treatment. Over the last few years, various laboratories have discovered particular activities of mammalian RAD52—both in S and M phase—that are distinct from the auxiliary role of yeast RAD52 in homologous recombination. At DNA double-strand breaks, RAD52 was demonstrated to spur alternative pathways to compensate for the loss of homologous recombination functions. At collapsed replication forks, RAD52 activates break-induced replication. In the M phase, RAD52 promotes the finalization of DNA replication. Its compensatory role in the resolution of DNA double-strand breaks has put RAD52 in the focus of synthetic lethal strategies, which is particularly relevant for cancer treatment.